2007
DOI: 10.1109/tpwrd.2007.899280
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Evaluation Based Approach to Replacement Strategy of Aged HVDC Components and Its Application at BCTC

Abstract: This paper presents a risk evaluation based approach to the replacement strategy of aged HVDC components. It includes estimation of unavailability of individual HVDC components due to aging failures, calculation of capacity state probabilities of the HVDC system, quantified risk evaluation of the power system containing the HVDC link and benefit/cost analysis for different replacement strategies. The presented approach can be also applied to other system components. The replacement strategy for an aged submari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The risk-based approach is an emerging new direction that is studied and beginning to be used in power system planning [35,36] and maintenance [37,38]. Most of previous work focus on the Risk-based Security Assessment (RBSA).…”
Section: The Need Of Risk-based Approach Under Uncertaintymentioning
confidence: 99%
“…The risk-based approach is an emerging new direction that is studied and beginning to be used in power system planning [35,36] and maintenance [37,38]. Most of previous work focus on the Risk-based Security Assessment (RBSA).…”
Section: The Need Of Risk-based Approach Under Uncertaintymentioning
confidence: 99%
“…This equivalence has been proved by two steps. First, it will be shown that (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) , as illustrated in Fig. 4.5.…”
Section: Probabilities Of Contingency (1) 'N-1' Contingencymentioning
confidence: 99%
“…As a developing new research direction, risk-based approach has been explored in certain research area on power system. References [3] and [4] describe the application of risk metric in obtaining power system planning schemes; references [5] and [6] implement risk-based theory in power system maintenance. It can be noted that most of the previous work are focused on riskbased security assessment (RBSA).…”
Section: Risk-based Optimal Power Flowmentioning
confidence: 99%
See 2 more Smart Citations